Design and Development of a Frequency Inverter with the Intel 80C196MC Microcontroller - Rivera Argoti, Pablo (2007)
This paper reports on the development of a frequency inverter for speed control of an induction machine. The control is implemented on a 80C196MC microcontroller and the power system is implement using a three-phase bridge of IGBTs. Both, control and power circuit provide an output with variable voltage and frequency. The frequency and other parameters in the speed drive are manipulated from a human-machine-interface HMI.